Heat dissipation in subterranean rodents: the role of body region and social organisation - Vejmělka, František; Okrouhlík, Jan; Lövy, Matěj; Šaffa, Gabriel; Nevo, Eviatar; Bennett, Nigel Charles; Šumbera, Radim (Scientific reports, 2021)
The relatively warm and very humid environment of burrows presents a challenge for thermoregulation of its mammalian inhabitants. It was found that African mole-rats dissipate body heat mainly through their venter, and social mole-rats dissipate more body heat compared to solitary species at lower temperatures. In addition, the pattern of the ventral surface temperature was suggested to be homogeneous in social mole-rats compared to a heterogeneous pattern in solitary mole-rats. To investigate this for subterranean rodents generally, we measured the surface temperatures of seven species with different degrees of sociality, phylogeny, and climate using infrared thermography. In all species, heat dissipation occurred mainly through the venter and the feet. Whereas the feet dissipated body heat at higher ambient temperatures and conserved it at lower ambient temperatures, the ventral surface temperature was relatively high in all temperatures indicating that heat dissipation to the environment through this body region is regulated mainly by behavioural means. Solitary species dissipated less heat through their dorsum than social species, and a tendency for this pattern was observed for the venter. The pattern of heterogeneity of surface temperature through the venter was not related to sociality of the various species. Our results demonstrate a general pattern of body heat exchange through the three studied body regions in subterranean rodents. Besides, isolated individuals of social species are less able to defend themselves against low ambient temperatures, which may handicap them if staying alone for a longer period, such as during and after dispersal events.
Keywords: Mole Rats; Hot Temperature; Behavior, Animal; vysoká teplota; Body Temperature Regulation; Species Specificity; druhová specificita; Rodentia; zvířata; hlodavci; mikroftalmičtí podzemní hlodavci; chování zvířat; termoregulace; Animals